Global expression profile of tumor stem-like cells isolated from MMQ rat prolactinoma cell. Issue 1 (December 2017) - Su, Zhipeng; Cai, Lin; Lu, Jianglong; Li, Chuzhong; Gui, Songbai; Liu, Chunhui; Wang, Chengde; Li, Qun; Zhuge, Qichuan; Zhang, Yazhuo
Abstract Background Cancer stem cells (CSCs), which have been isolated from various malignancies, were closely correlated with the occurrence, progression, metastasis and recurrence of the malignant cancer. Little is known about the tumor stem-like cells (TSLCs) isolated from benign tumors. Here we want to explore the global expression profile of RNA of tumor stem-like cells isolated from MMQ rat prolactinoma cells. Methods In this study, total RNA was extracted from MMQ cells and MMQ tumor stem-like cells. RNA expression profiles were determined by Agilent Rat 8 × 60 K Microarray. Then we used the qRT-PCR to test the result of Microarray, and found VEGFA had a distinct pattern of expression in MMQ tumor stem-like cells. Then WB and ELISA were used to confirm the VEGFA protein level of tumor sphere cultured from both MMQ cell and human prolactinoma cell. Finally, CCK-8 was used to evaluate the reaction of MMQ tumor stem-like cells to small interfering RNAs intervention and bevacizumab treatment. Result The results of Microarray showed that 566 known RNA were over-expressed and 532 known RNA were low-expressed in the MMQ tumor stem-like cells. These genes were mainly involved in 15 different signaling pathways. In pathway in cancer and cell cycle, Bcl2, VEGFA, PTEN, Jun, Fos, APC2 were up-regulated and Ccna2, Cdc25a, Mcm3, Mcm6, Ccnb2, Mcm5, Cdk1, Gadd45a, Myc were down-regulated in the MMQ tumor stem-like cells. The expression of VEGFA were high in tumor spheres cultured from both MMQ cell and human prolactinomas. Down-regulation of VEGFA by small interfering RNAs partially decreased cell viability of MMQ tumor stem-like cells in vitro. Bevacizumab partially suppressed the proliferation of MMQ tumor stem-like cells. Conclusions Our findings characterize the pattern of RNA expression of tumor stem-like cells isolated from MMQ cells. VEGFA may act as a potential therapeutic target for tumor stem-like cells of prolactinomas.